Determinants of Academic Stress of Elementary School Students in Digital Learning and the Role of Counseling - Ade Herdian Putra; Zadrian Ardi; Mutia Yollanda (Pedagogik Journal of Islamic Elementary School, 2025)
This research seeks to identify the key determinants of academic stress experienced by elementary students within the framework of digital-based education. At the elementary school level, especially for higher grade students, digital learning often poses new challenges that are not only technical, but also emotional. Intensive use of digital media can lead to overload learning and device dependence, which in turn increases academic stress. A quantitative method with a confirmatory framework was employed in this research to validate a conceptual model that includes overload learning, nomophobia, and academic self-efficacy as key variables. Data were obtained from 290 elementary school students in West Sumatra Province through an online questionnaire developed from previously valid instruments. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Findings indicated that both overload learning and nomophobia were positively and significantly associated with academic stress. On the other hand, academic self-efficacy contributed to lowering stress and served as a moderating factor in the relationships among the variables. The findings suggest that elementary school students need adequate psychosocial support, and guidance and counseling services in elementary schools are crucial in helping them manage academic stress in today's digital era.